Radikalisme dan Terorisme Berdasarkan Perspektif Tafsir Maudhu’i - Eca Dwi Yandra; Gery Hummamul Hafid; Kaka Reza Abdullah; Luthfatul Millah; Asep Abdul Muhyi (Gunung Djati Conference Series, 2023)
This study aims to discuss Islam, radicalism and terrorism. This research uses descriptive methodology and maudhu'i interpretation. This particular qualitative approach is based on secondary data sources, namely literary works that are relevant to the research problem and sourced from books, journals, articles and other sources. Inventory, classification, and interpretation steps were used in data analysis. Validity checking technique Using library research is a method used to verify the confidentiality of data. Based on the research results, the author has made various discoveries, including issues regarding Islam, Radicalism, and Terrorism and found the results of research on the verses of the Qur'an with Tasir maudhu'i relating to Islam, Radicalism, and Terrorism.